UPAYA MENINGKATKAN VOLUME PENJUALAN PADA PT. SINAR SOSRO PALEMBANG - Hasyunah Hasyunah; Yasmina Martini (JURNAL KOMPETITIF, 2022)
The company's competition will be sharper along with the increasing number of companies that produce the same product. In carrying out its activities, companies need marketing in order to achieve their goals because marketing activities are one of the activities carried out by companies that aim to provide goods and services for consumers. Likewise PT. Sinar Sosro Palembang which is a private company engaged in the sale of ready-to-drink beverages. If the company does not use good marketing, the company will experience various difficulties in marketing its products. To be able to increase sales volume is not easy, given the increasingly fierce competition between companies. Companies can anticipate from the start in implementing the right product sales strategy to face competition between companies, especially in similar companies. For this reason, companies must be able to take an innovative step in meeting comfort and ensuring safety.Keywords : Marketing Activities; Sales Volume; Sales Strategy